Clinical Effectiveness and Potential Survival Benefit of US-Guided High-Intensity Focused Ultrasound Therapy in Patients with Advanced-Stage Pancreatic Cancer - Marinova, Milka; Huxold, Hannah C.; Henseler, Jana; Mücke, Martin; Conrad, Rupert; Rolke, Roman; Ahmadzadehfar, Hojjat; Rauch, Maximilian; Fimmers, Rolf; Luechters, Guido; Cuhls, Henning; Radbruch, Lukas; Schild, Hans H.; Strunk, Holger (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose Pancreatic cancer (PaC) is a life-limiting tumor with a wide range of incapacitating symptoms such as cancer pain in more than 80 % of patients. This prospective interventional study addresses the clinical effectiveness of ultrasound-guided high-intensity focused ultrasound (HIFU) treatment for patients with advanced-stage PaC, including pain perception, tumor size and survival benefit.Materials and Methods 50 patients with late-stage PaC underwent HIFU. Clinical assessment included evaluation of tumor volume by imaging and pain burden (pain severity, pain sensation, interference with daily activities) using the Brief Pain Inventory at baseline and follow-up. Median overall survival, progression-free survival and time to local progression were estimated using Kaplan-Meier analysis.Results In 84 % of patients, significant early relief of cancer-induced abdominal pain was achieved by HIFU independent of metastatic status; it persisted during follow-up. Tumor volume reduction was 37.8 ± 18.1 % after 6 weeks and 57.9 ± 25.9 % after 6 months. 21 % of HIFU-treated patients had local tumor progression with a median time of 14.4 months from intervention. The median overall survival and progression-free survival were 16.2 and 16.9 months from diagnosis and 8.3 and 6.8 months from intervention.Conclusion In patients with advanced pancreatic cancer and otherwise limited treatment options, HIFU resulted in significant early and long-lasting pain relief and tumor size reduction over time independent of metastatic status. Clinical data suggest an additional potential survival benefit.
Keywords: abdomen; pancreatic carcinoma; high-intensity focused ultrasound; therapeutic ultrasound; pain management